Occupational Stress of Employees with Special Reference to Private Companies in Coimbatore - Dr.M.Punitha, P. Natarajan, (International Journal of Scientific Research and Management (IJSRM), 2017)
Occupational Stress is a mind-body stimulation that can, on the other tiredness body systems to the point of malfunction and syndrome of the employees. Occupational Stress is both physical response that protects us and a natural defense mechanism that has allowed our species to endure. Strains generally classified as psychological, physical, or behavioral examples of commonly studied psychological strains include such things as job dissatisfaction, anxiety, and depressed mood. Finally, behavioral strains include such things as absenteeism, poor performance, and turnover of the employees. That means occupational stress can be motivating, energizing, and exciting us to greater endeavor of the employees. Descriptive research design and simple random sampling technique lottery method was adopted for the study. A sample size of 354 employees was collected using Questionnaire. Occupational Stress Scale developed by A. K. Srivastava and A.P. Singh (1984). Department of Psychology, Banaras Hindu University Varanasi, This schedule has 46 statements and 5 point scale. This study concludes that 76 percent of the respondents have moderate level of occupational stress, 13.8 percent of the respondents have low level of occupational stress, and 10.2 percent of the respondents have high level of occupational stress.